1997
DOI: 10.1097/00006199-199703000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity, Emotional Well-Being, And Family Functioning as Determinants of Family Satisfaction In Caregivers of Elderly Parents

Abstract: The purpose of this study was to test a theoretical model developed to explain family satisfaction among 171 caregivers of elderly parents. Using LISREL to estimate path coefficients, the findings support family satisfaction as directly and indirectly influenced by reciprocity, emotional well-being and family functioning. Explanatory variables accounted for 70% of the variance in predicting family satisfaction. Intrinsic rewards derived from giving care, positive affect, and family functioning contributed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 38 publications
9
39
0
Order By: Relevance
“…New outcomes include personal growth, skill building, a stronger sense of purpose, and deepened intimacy. Significantly, these experiences are associated with heightened quality of life and greater satisfaction in relationships (Carruth et al, 1997). Ultimately, then, the findings suggest that three core components of social work practice, the family systems approach, the strength perspective, and use of self can support care partnerships affected by dementia in important ways.…”
Section: Discussion: Social Work Dementia and Quality Of Lifementioning
confidence: 93%
See 1 more Smart Citation
“…New outcomes include personal growth, skill building, a stronger sense of purpose, and deepened intimacy. Significantly, these experiences are associated with heightened quality of life and greater satisfaction in relationships (Carruth et al, 1997). Ultimately, then, the findings suggest that three core components of social work practice, the family systems approach, the strength perspective, and use of self can support care partnerships affected by dementia in important ways.…”
Section: Discussion: Social Work Dementia and Quality Of Lifementioning
confidence: 93%
“…Focusing on levels of cognitive and physical capacity highlights areas of deficit and the demands of daily living with dementia (Banerjee et al, 2006;Ready & Ott, 2003;Ryan, Nolan, Reid, & Enderby, 2008). However, when quality of life is measured in terms of relatedness, such as of shared moments rather than memories; feelings rather than thoughts; and focusing on what remains rather than what is lost, it becomes available again to families affected by dementia (Carruth, Tate, Moffett, & Hill, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As the caregivers are able to derive rewards from care provision, other family members may benefit tangentially. Carruth, Tate, Moffett, and Hill (1997) found that family satisfaction was directly related to the individual's ability to find happiness and contentment within the caregiving role.…”
Section: Discussionmentioning
confidence: 98%
“…In turn, increased family satisfaction generally contributes to a higher quality of life [10]. Family satisfaction has been shown to be important to those who have sustained a severe injury [11][12][13].…”
Section: Introductionmentioning
confidence: 99%